Response of Nutrient Management and Moisture Conservation Practices on Growth and Yield of Mustard Under Rainfed Condition - Yogesh Singh,; V.K. Kanaujia,; H.P. Chaudhary, (Journal of Soil and Water Conservation, 2022)
Present study was laid out under rainfed condition to find the response of nutrient management and moisture conservation practices on growth and yield of mustard. Both the  practices exhibited significant effect on growth and yield attributes, yield of grain and Stover and harvest index of mustard during both the years of experimentation except, plant stand which was higher under treatments over control, Plant population, plant height, Number of branches per plant, length of siliqua, number of siliqua per plant, Number of seed per siliqua and 1000 seed weight, grain and Stover yield and harvest index were increased with increasing plant nutrients in combination. All these parameters were maximized under treatment of N660-+P30+S20 Kgha-1. Paddy straw mulch @ 3 tha-1 brought maximum response in growth and yield characteristics, grain and Stover yield and harvest index of mustard in comparison to other moisture conservation practices.